2022
DOI: 10.1029/2021je007153
|View full text |Cite
|
Sign up to set email alerts
|

High‐Resolution Thermophysical Analysis of the OSIRIS‐REx Sample Site and Three Other Regions of Interest on Bennu

Abstract: The OSIRIS‐REx (Origins, Spectral Interpretation, Resource Identification, and Security–Regolith Explorer) spacecraft sampled asteroid (101955) Bennu on 20 October 2020 and will return the collected regolith to Earth in 2023. Before sample collection, spectral observations of four regions of interest on Bennu's surface were acquired at high spatial resolution (2–9 m per spectrometer spot) to identify the most suitable site for sampling and provide contextual information for the returned sample. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 78 publications
2
17
0
Order By: Relevance
“…As a caveat, additional analyses may reveal more variation within the boulder groups than is apparent from this study. For example, Rozitis et al (2022) described two boulders along the edge of Hokioi Crater that look similar but have quite distinct thermal inertia values. This difference could be attributed to different inherent properties, or could rather be due to varying degrees of surficial weathering, ejecta or fine-grained particle coating, or other superficial effects.…”
Section: Discussionmentioning
confidence: 99%
“…As a caveat, additional analyses may reveal more variation within the boulder groups than is apparent from this study. For example, Rozitis et al (2022) described two boulders along the edge of Hokioi Crater that look similar but have quite distinct thermal inertia values. This difference could be attributed to different inherent properties, or could rather be due to varying degrees of surficial weathering, ejecta or fine-grained particle coating, or other superficial effects.…”
Section: Discussionmentioning
confidence: 99%
“…Observations of Bennu's surface and the TAGSAM head taken before, during, and after sample acquisition (e.g., Lauretta et al., 2022; Walsh, Ballouz, et al., 2022; Walsh, Bierhaus, et al., 2022) showed particles ranging from dust to gravel. The centimeter‐scale stones wedged in the TAGSAM flap indicate strength of individual particles, but Bennu's thermal inertia indicates weak, porous rocks (Rozitis et al., 2022). It is unknown to what extent the particles might be disrupted during atmospheric entry, descent, and landing.…”
Section: Future Planningmentioning
confidence: 99%
“…The selected sampling site, known by the team as Nightingale, is located within Hokioi crater in Bennu's northern hemisphere (Lauretta et al., 2021, 2022). This site presented an opportunity to sample Bennu in a location with a variety of particle reflectances suggestive of different lithologies (Lauretta et al., 2022), a relatively recent exposure age (DellaGiustina et al., 2020), and a low peak surface temperature (Rozitis et al., 2022), increasing the likelihood of sampling volatile‐ and organic‐rich material. Sampling was accomplished on the first attempt on October 20, 2020 (Lauretta et al., 2022; Walsh, Ballouz, et al., 2022), and the spacecraft departed Bennu on May 10, 2021, for a 28‐month return journey back to the Earth.…”
Section: Introductionmentioning
confidence: 99%
“…In an exception to these trends, the spatially resolved measurements of the C-type near-Earth asteroids (101955) Bennu (Rozitis et al 2020b(Rozitis et al , 2022 and (162173) Ryugu (Okada et al 2020;Shimaki et al 2020) have recently revealed that rock porosity also dictates the thermal inertia for at least these two asteroids. It has been hypothesized that such asteroids, comprising porous rocks and boulders, produce less particulate regolith from mechanical space weathering processes, such as thermal cracking and micrometeorite bombardment (Cambioni et al 2021).…”
Section: Introductionmentioning
confidence: 99%